Preparation, characterization and in vitro cytotoxicity evaluation of free and liposome-encapsulated tylosin - Saddiqi, Mohammad Ehsan; Abdul Kadir, Arifah; Abdullah, Faez Firdaus Jesse; Abu Bakar Zakaria, Md Zuki; Banke, Idris Sherifat (Elsevier BV, 2022)
Liposomes are the most attractive and well-known nanoparticles due to their high biocompatibility and biodegradability features which make them display less toxic effects for employing in vivo. Encapsulation of antibiotics within liposomes can provide a promising strategy for the effective treatment of resistant bacterial pathogens. This research was performed to prepare, characterize and evaluate the in vitro cytotoxicity effect of free and liposomal tylosin. Liposomal tylosin was produced by the thin-film hydration method. The characterization was performed by dynamic light scattering and high resolution transmission electron microscopy. Methylthiazol tetrazolium (MTT) assay was applied to evaluate the cytotoxicity of free and liposome-encapsulated tylosin against the NIH3T3 and NHDF. The obtained findings indicated well-formed liposome with ideal characteristics that efficiently encapsulated tylosin. The cytotoxicity data revealed cell viability of above 70% for liposomal tylosin and below 70% for free tylosin towards both NIH3T3 and NHDF at concentration of 1024 µg/mL. Therefore, liposome is a promising vehicle for an antibiotic delivery system with appropriate physicochemical, drug loading, release characteristics, and ideal biocompatibility properties.